The lies I tell : a novel - Clark, Julie, 1971- (Sourcebooks Landmark, 2022)
"Meg Williams. Maggie Littleton. Melody Wilde. Different names for the same person, depending on the town, depending on the job. She's a con artist who erases herself to become whoever you need her to be. A college student. A life coach. A real estate agent. But nothing about her is real. She slides alongside you and tells you exactly what you want to hear, and by the time she's done, you've likely lost everything. Kat Roberts has been waiting ten years for the woman who upended her life to return. And now that she has, Kat is determined to be the one to expose her. But as the two women grow closer, Kat's long-held assumptions begin to crumble, leaving Kat to wonder who Meg's true target is. The Lies I Tell is a twisted domestic thriller that dives deep into the psyches and motivations of two women and their unwavering quest to seek justice for the past and rewrite the future"--